Primary antiphospholipid syndrome associated Liebman-Sachs endocarditis leading to diffuse alveolar hemorrhage: A case report. (2018) - Hyde, Ryan; Runnstrom, Martin; Anderson, Austin; Riley, Leonard; Ataya, Ali
Abstract: A 26 year old female presented for recurrent blood tinged sputum during the previous year with development of frank hemoptysis three days prior to admission. Diffuse alveolar hemorrhage (DAH) was confirmed with serial lavages. The patient had no history of autoimmune disease, vascular thrombosis or pregnancy morbidity including miscarriages or pre-eclampsia. High dose steroids were initiated along with noninvasive ventilatory support. Transthoracic echocardiogram showed severe mitral regurgitation and a vegetation on the mitral valve; transesophageal echocardiogram determined the lesion highly suggestive of Libman-Sachs endocarditis. Blood cultures were negative. Immunological evaluation established the patient was negative for: anti-nuclear antibody, anti-double-stranded DNA antibody, rheumatoid factor, anti-smith antibody, anti-cyclic citrullinated peptide, anti-neutrophil cytoplasmic antibodies, anti-glomerular basement membrane antibodies. Further evaluation revealed elevated levels of anticardiolipin immunoglobulin G and anti-beta 2 glycoprotein immunoglobulin G which continued to increase for months after hospitalization. She was diagnosed with DAH secondary to acute mitral regurgitation caused by Libman-Sachs endocarditis in the presence of primary antiphospholipid antibody syndrome. DAH is an important disease to understand given its high mortality rate. Few case reports relating the presence of Libman-Sachs endocarditis induced by antiphospholipid antibody syndrome leading to DAH have been published. Unique here is the absence of rheumatologic markers thus supporting a diagnosis of primary antiphospholipid antibody syndrome (APS). This patient had no findings associated with rheumatological disorders potentially making this diagnosis easily overlooked. This case further illustrates the importance of evaluating patients with APS presenting with DAH as there are multiple etiologies that lead to this pathology thus different treatment avenues are to be considered during management.